Kepuasan ibu hamil terhadap rawatan Penjagaan kejurura watan di wad Antenatal Hospital Universiti Sains Malaysia (HUSM) - Faridah, Zulkifli (PPSP, Universiti Sains Malaysia, 2007)
Introduction: Patient's satisfaction is the most important factor to assure quality in health care. Assessment towards a nurse is vital because patient's satisfaction is mostly influenced by their experience involving nurse. Health care aspects of nursing care that usually being assessed are altitude, time spending, communication, information giving, health education and skill. Objective: This research done to determine a pregnant women's satisfaction toward the aspects of nursing care that is skill, education, information giving, caring and wellmannered attitude in the antenatal ward in HUSM. Beside this research is to determine the association of social demographic factor such as race, religion, education level, working status, salary status and number of chill with level of pregnant women's satisfaction toward nursmg care. Methodology: This study is a quantitative study with descriptive using cross sectional structure. About 90 pregnant women involved in this research. The instrument used is Consumer Emergency Department Care Satisfaction (CECSS). Result: The majority of the pregnant women's were satisfied with the nursing care. In this research all aspects that are the skill, education, information giving and polite attitude show very high level of satisfaction. Analysis of the social demographic factor show that the factor of working status and number of chill show significant relationship with satisfaction relationship with satisfaction of pregnant women's toward nursing care .Other factor such as age, race, religion, and the income average shows no significant relationship toward nursing care .It is found that the caring attitude gained less percentage compared to the other aspect of the study. Conclusion: Every aspect of the nursing which are skill, education, information giving, caring and polite attitude should be given in the best manner to mother. Nurse also must aware of the social demographic factors that would affect level of satisfaction.